Surface Chemical Structure and Morphological Analysis of Fallen Teak Leaves (Tectona grandis) Powder for Methylene Blue Adsorption - Hikmawati, Dwi Ima; Haqiqi, Embun Rachma (CHEESA: Chemical Engineering Research Articles, 2019)
In recent year, theresearch focushas been shiftedtoward developingof an environmentally friendly system toeliminateany pollutantsfrom Waste.The potential of fallen teak leavespowder for removal of methylene blue has beensuccesfullycarried out by batch adsorption system. The purposeof this study is to characterize an adsorbent obtained from local fallen teak leaves.The characterization focused on the surface of chemical structure analysis obtained fromFourier Transform Infrared (FTIR) spectroscopy and morphologicalanalysis by Scanning Electron Microscopy (SEM)in order to get an idea fuctional group as active site andtextural properties.The FTIR resultshave explanedthe presence of some functional groups such as –OH, C=C, COO–, CO, NO2on FTLP surface that could be potential adsorption sites for interaction with MB molecules. The SEM photographs morphology of FTLP surface has a rough surface with almost more non-uniform